Comparison of phenolic extracts obtained of Pinus radiata bark from pulp and paper industry and sawmill industry - Aspé, Estrella; Fernández, Katherina (Maderas. Ciencia y Tecnología, 2025)
Pinus radiata barks obtained from tress of different ages, as subproduct of pulp and paper (trees less than 10 years) and sawmill (trees between 20 to 25 years) industries, were used to produce extracts containing phenolic compounds. A factorial design 23 was used to evaluate the influence of the variables temperature (25 – 35 ºC), solvent type (acetone - ethanol) and extraction time (1-12 h). The extracts were compared in their extraction yield (%), total phenols (by FolinCiocalteau), and radical scavenging activity (by DPPH). The extract obtained from old trunks presented a higher extraction yield than from young trees. The highest yield value was 2.56%, which was obtained using acetone as solvent for 12 h and 35°C. The highest concentration of phenol (5.84±0.18 g CE g extract-1), and scavenging activity (IP=86.1±4.4%) were also obtained for this type of extract. The extraction duration was the variable that most influenced the parameters studied. The bark’s radical scavenging power was greater than BHT (40%) and slightly lower than ascorbic acid (92%), common commercial antioxidants.